The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/1753465812452193
|View full text |Cite
|
Sign up to set email alerts
|

New treatment options for multidrug-resistant tuberculosis

Abstract: Despite the development of effective treatments, tuberculosis (TB) remains a major health problem. TB continues to infect new victims and kills nearly 2 million people annually. The problem is much greater in resource-limited countries but is present worldwide. Inadequate public health resources, cost, the obligatory long treatment period, and adverse drug effects contribute to treatment failures and relapses. Drug-resistant Mycobacterium tuberculosis (MTB) strains arise spontaneously and are propagated by ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 117 publications
(327 reference statements)
0
34
0
5
Order By: Relevance
“…Some of these newer compounds include oxazolidinones, nitroimidazopyrans, diarylquinolones, pyrrols, ethenylenediamines, ethylenediamides, and benzothiaziones. [88][89][90]. Linezolid, a broad spectrum antibiotic that inhibits protein synthesis by interfering with mRNA binding to the ribosome is currently in phase II trials for the treatment of MDR-TB [87,88].…”
Section: Drug-susceptible Tb [71]mentioning
confidence: 99%
See 3 more Smart Citations
“…Some of these newer compounds include oxazolidinones, nitroimidazopyrans, diarylquinolones, pyrrols, ethenylenediamines, ethylenediamides, and benzothiaziones. [88][89][90]. Linezolid, a broad spectrum antibiotic that inhibits protein synthesis by interfering with mRNA binding to the ribosome is currently in phase II trials for the treatment of MDR-TB [87,88].…”
Section: Drug-susceptible Tb [71]mentioning
confidence: 99%
“…[88][89][90]. Linezolid, a broad spectrum antibiotic that inhibits protein synthesis by interfering with mRNA binding to the ribosome is currently in phase II trials for the treatment of MDR-TB [87,88]. Although no large clinical trials have been conducted to date, several small studies indicated that treatment regimens that include Linezolid can be used to successfully treat infections due to MDR-TB [88].…”
Section: Drug-susceptible Tb [71]mentioning
confidence: 99%
See 2 more Smart Citations
“…3 This is the first time in the modern history of TB control that new drugs have been developed and approved for the treatment of MDR-TB, and the first time that national and international TB stakeholders have tried to introduce new drugs in a programmatic way. 4 Uptake of these drugs as part of MDR-TB treatment, however, has not kept pace with the need for these drugs, even in settings where resistance or intolerance to second-line drugs is common or where treatment outcomes are poor. 5 Multiple early barriers to programmatic introduction of new drugs have been identified, including lack of technical expertise and guidance, confusion about pharmacovigilance requirements, challenges with registration and import, and difficulties in obtaining the other medications needed for successful treatment outcomes.…”
mentioning
confidence: 99%